Decreased Epithelial Cytokine Responses in the Duodenal Mucosa of Helicobacter pylori-Infected Duodenal Ulcer Patients - Strömberg, E. (American Society for Microbiology, 2003)
Helicobacter pylori colonizes the human stomach and areas of gastric metaplasia in the duodenum, but only a minority of those that are infected develop symptoms, e.g., peptic ulcers. Although most ulcers occur in the duodenum, almost all studies of mucosal immune responses against the infection have been limited to responses in the stomach. In the present study we evaluated whether there are differences in the levels of proinflammatory cytokines as well as immunoregulatory cytokines in the duodenal mucosa of duodenal ulcer (DU) patients and asymptomatic (AS) carriers which may be related to the development of duodenal ulcers. Duodenal biopsy specimens collected from normal mucosa as well as metaplastic mucosa of DU patients, AS carriers, and uninfected controls were analyzed for a number of cytokines by immunohistochemistry. Interestingly, the level of epithelial staining for several cytokines, e.g., interleukin-8 (IL-8), transforming growth factor β (TGF-β), and gamma interferon (IFN-γ), was found to be significantly lower in DU patients than in AS carriers and uninfected individuals. No differences were observed when cytokine staining in normal and metaplastic biopsy specimens was compared. However, larger numbers of IL-8-, IL-6-, TGF-β-, and IFN-γ-positive mononuclear cells were observed in the duodenal lamina propria of both DU patients and AS carriers than in that of the uninfected controls. Our finding that a number of cytokines that may be important for the mucosal host defense against H. pylori are strongly decreased in the duodenal epithelium of ulcer patients suggests that a down-regulated immune response plays a role in the development of duodenal ulcers.